Addition of Organometallic Reagents to Chiral N‐Methoxylactams: Enantioselective Syntheses of Pyrrolidines and Piperidines. Issue 49 (21st October 2013) - Jäkel, Mascha; Qu, Jianping; Schnitzer, Tobias; Helmchen, Günter
Abstract Enantioselective iridium‐catalyzed allylic substitutions were used to prepare N‐allyl hydroxamic acid derivatives that were suitable for ring‐closing metathesis, giving N‐methoxylactams. Reactions of these derivatives with Grignard or organolithium compounds gave hemiaminals, which could be reduced diastereoselectively via acyliminium intermediates to give cis‐piperidines or cis‐pyrrolidines with substituents in the 2, 6‐ or 2, 5‐positions, respectively. In addition, compounds with a quaternary carbon center could be synthesized by corresponding reactions with potassium cyanide/AcOH. The procedures were applied in the syntheses of alkaloids (−)‐209D and (+)‐prosophylline.